Penetapan Kadar Kafein Ekstrak Daun Teh Hijau Dan Putih Camellia Sinensis (L.) Dengan Kromatografi Cair Kinerja Tinggi - Selfia Lestary; Muhammad Amin Nasution; Ridwanto Ridwanto; Haris Munandar Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Tea, a widely popular and frequently consumed beverage, is integral to daily routines. Despite the potential long-term risks associated with excessive caffeine consumption, such as hypertension, heart disease, and stroke, caffeine is a prominent choice among a diverse spectrum of individuals in society. The objective of this research endeavour is to discern the caffeine content present in extracts derived from green and white tea leaves by applying the high-performance liquid chromatography (HPLC) method. The research procedure encompasses a series of stages, encompassing the preparation of botanical materials, extraction employing ethanol solvent, characteristic analysis, phytochemical screening, and quantification of caffeine levels within the green and white tea leaf extracts utilising the HPLC technique. The extraction process of green and white tea leaves entails maceration utilising 96% ethanol, followed by concentration via a rotary evaporator. The determination of caffeine concentrations is executed using the high-performance liquid chromatography method. A phytochemical screening analysis of ethanol extracts derived from green and white tea leaves unveiled a myriad of chemical compound classes, including alkaloids, flavonoids, saponins, tannins, and steroids. The quantification of caffeine content within the samples is ascertained by calculating the area under the curve (AUC) on the chromatograms of green and white tea extracts. The quantification results for caffeine content in the green tea extract reveal a value approximately equivalent to 98.4278069571 mg/g. The white tea extract demonstrates a content value of approximately 136.131488681 mg/g.